Determine the controls for nomination to the list of international football referees - حسين, رعد; قاسم خلف, صباح; مهنا عناد, سمير (Journal of Physical Education, 2019)
To call FIFA from Unions National every year from September month to send list of referees International to reliance they next year and have start the problems to choose the referees maybe created according public relations and the researcher notice there avow nonbeing strictness of choose referees therefore to consider definition special controls according to foundations learned academy The list of FIFA from application special to be complete determination and definition the best calculation to regard the expert and to discuss and referees number(50) time 1 5-2572007 and definition better condition special the referee from to compete between the referees to condition scientific basis